Plasmon-exciton coupling regimes in MoS2 monolayers on gold gratings: a reflectance analysis via FDTD simulations - Oliveira, Willer Frank de Sousa (2025)
This work aimed to investigate the regimes and coupling in hybrid systems composed of a molybdenum disulfide (MoS2) monolayer coupled to different metallic gold nanostructures, using numerical simulations based on the Finite-Difference Time-Domain (FDTD) method, complemented by experimental differential reflectance measurements. The MoS2 monolayer, a two-dimensional semiconductor with a direct bandgap in the visible region, exhibits well-defined excitonic excitations, notably the A and B excitons. By engineering the geometric parameters of the metallic gratings such as periodicity (Λ), depth (d), and slit width (w) it was possible to tune the plasmonic resonances to coincide with the excitonic energies of the MoS2 monolayer. The optimal parameters were determined as Λ = 400 nm, d = 70 nm, and w = 50 nm, with the most favorable excitation condition occurring at an incidence angle of 50°. Among the most relevant indications of a possible strong-coupling regime is the observation of behavior consistent with the anti-crossing phenomenon in the simulated spectra, which may be related to Rabi splitting and the formation of hybrid states, known as plexcitons. Although these results are promising, additional studies are needed to unequivocally confirm the occurrence of strong coupling. These findings contribute to the understanding and development of hybrid plasmon-exciton platforms for applications in nanophotonics, with potential impact on the design of photodetectors, high-sensitivity optical sensors, ultrafast modulators, nanoscale coherent light sources, and the enhancement of nonlinear optical processes, such as Second Harmonic Generation (SHG), in two-dimensional materials.